Effects of beet juice supplementation in different concentrations and the importance of nitric oxide in endurance runners - Serrano, Richard Danilo; Fioravante Victor, William; Maesta, Nailza; Elias Diniz, Rodrigo; Maluf Morelato, Laurita; Souza Campos, Isabela; l dos Santos Canciglieri, Raphae (Open Science Journal, 2023)
More and more beetroot has been highlighted in sports, mainly in long-term aerobic modalities, due to its high concentration of nitrate (NO3- ), being an important precursor of nitric oxide (NO), providing an improvement in sports performance. The main objective of this study was to investigate the effects of acute ingestion of beetroot juice (BR), rich in NO3- in different concentrations in endurance exercise, evaluating performance, glycemic, cardiorespiratory and urinary responses of amateur runners. We hypothesized that BR would increase glucose uptake, minimize VO2max (maximum oxygen uptake), improve exercise economy and runners' performance. Nineteen male amateur runners were exposed to two conditions, ingestion of BR and PL (placebo), the individuals were divided into three groups (minimum, average and maximum concentration), being submitted to a 30-minute running test at maximum intensity, on a racetrack. Pre and posttest blood and urine samples were collected to determine glucose uptake, NO2- (nitrite) excretion, urinary pH and urinary density. Cooper's test also performed in order to assess VO2max. The main posttest results showed that through nitrite excretion there was a reduction of nitrate to nitric oxide (0 ± 0 vs 0.94 ± 0.23, P <0.05 (pre vs post)), increase in glucose uptake (139.94 ± 35.02 vs 122.88 ± 37.69, P <0.05 (PL vs BR)) and VO2max improvement(54.96 ± 6.87 vs 55.99 ± 6.88, P <0.05 (PL vs BR))], coinciding with the increase in physical performance (2972.63 ± 308.84 vs 3018.95 ± 309.29, P <0.05 (PL vs BR))]. The results found observed that beet supplementation in amateur runners increased glucose uptake, improved VO2max and running performance.